Evaluasi Gerakan Orang Tua Asuh Cegah Stunting dengan Model CIPP di Kelurahan Tamarunang Gowa - Rahmaniah Usman; Andi Atssam Mappanyukki; Andi Nurzakiah Amin (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2026)
Stunting remains a public health problem in Indonesia, including in Gowa Regency. The Genting Program is a collaborative innovation involving Foster Parents (OTA) to assist families at risk of stunting. However, the effectiveness of this program has never been comprehensively evaluated. This study aims to evaluate the implementation of the Genting Program using the CIPP Model (Context, Input, Process, and Product). This study used qualitative research with a case study approach. 15 informants consisted of program managers, local government officials at the village level, cadres, OTAs, and target families. Data were collected through in-depth interviews, observation, and documentation, then analyzed thematically. The results of the study on the context aspect indicate that the program is in accordance with national policies and local needs, supported across sectors with 37 target families. The input aspect shows that there is support from cadres, OTAs, and the government with voluntary funding and adequate infrastructure. The process aspect shows that mentoring activities, nutrition education, and child growth monitoring are running, but are hampered by low community interest in becoming OTAs and limited funds. The product aspect shows that the program improves nutritional knowledge, parenting patterns, awareness of growth monitoring, and children's nutritional status, although sustainability is not yet optimal. This study concludes that the Gentinf Program makes a positive contribution to stunting prevention, but still faces obstacles in terms of community participation and funding.